2018
DOI: 10.1152/ajplung.00429.2017
|View full text |Cite
|
Sign up to set email alerts
|

FABP4 regulates eosinophil recruitment and activation in allergic airway inflammation

Abstract: Fatty acid binding protein 4 (FABP4), a member of a family of lipid-binding proteins, is known to play a role in inflammation by virtue of its ability to regulate intracellular events such as lipid fluxes and signaling. Studies have indicated a proinflammatory role for FABP4 in allergic asthma although its expression and function in eosinophils, the predominant inflammatory cells recruited to allergic airways, were not investigated. We examined expression of FABP4 in murine eosinophils and its role in regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 73 publications
3
29
0
Order By: Relevance
“…Its role in chronic respiratory diseases is poorly understood, although it has been recognized that FABP4 is associated with airway inflammation [19]. Likewise, a dysregulation of airway FABP4 has been previously described in asthma [20] where it has been shown in experimental models that FABP4 participates in the recruitment and activation of eosinophils [21]. In patients with COPD, a dysregulation of systemic FABP4 compared with controls has been suggested [22], which is at variance with our findings here.…”
Section: Previous Studiessupporting
confidence: 55%
“…Its role in chronic respiratory diseases is poorly understood, although it has been recognized that FABP4 is associated with airway inflammation [19]. Likewise, a dysregulation of airway FABP4 has been previously described in asthma [20] where it has been shown in experimental models that FABP4 participates in the recruitment and activation of eosinophils [21]. In patients with COPD, a dysregulation of systemic FABP4 compared with controls has been suggested [22], which is at variance with our findings here.…”
Section: Previous Studiessupporting
confidence: 55%
“…FABP4 was observed in lung tissue only. Past studies have shown that FABP4 in lungs regulates the eosinophil recruitment and activation [60] , and induces vascular remodeling and angiogenesis in allergic asthma [37] . Our study discovered that the first inflammatory reaction would begin when the allergen enters through the airway with disrupted barrier, where FABP5 is strongly expressed.…”
Section: Discussionmentioning
confidence: 99%
“…3 ). FABP4 has been shown to be expressed in lung and bronchoalveolar cells in bronchopulmonary dysplasia 116) , lung lavage cells in sarcoidosis 117) , bronchial epithelial cells 118) and vascular endothelial cells 119) in asthma, eosinophils in allergic airway inflammation 120) , microglia cells in neuroinflammation 121) , resident macrophages/microglial cells and endothelial cells of the hyaloid vasculature in the immature retina of proliferative retinopathy 122) , pulmonary artery endothelial cells in pulmonary thromboembolism 123) , hepatocytes in liver ischemia/reperfusion injury 124) , human placental trophoblasts during placental development 125) , and granulosa cells of the ovary in polycystic ovary syndrome 126, 127) . Furthermore, FABP4 has been detected in human ovarian cancer cells at the adipocyte-tumor cell interface, and FABP4 deficiency in mice substantially impaired metastatic tumor growth 128) .…”
Section: Ectopic Expression Of Fabp4mentioning
confidence: 99%